PENGEMBANGAN OLAHAN HASIL TERNAK MELALUI DIVERSIFIKASI PRODUK BERBAHAN DASAR SUSU DI KELURAHAN CEPOKO GUNUNGPATI SEMARANG - Yuniastuti, Ari; Setiati, Ning; Susanti, R (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
Kelurahan Cepoko is one of 16 urban villages in Gunungpati sub-district. The source of income of Cepoko village residents is in the field of livestock, as much as 77 residents of Cepoko urban village who rely their life in the field of farms, both chicken farms, dairy cows and meat cows. Dairy cattle breeding activities do not provide sufficient income, because the selling price of milk purchased by cooperatives is too cheap, so it can not cover operational costs. Therefore, one of the citizens of SME RW 09 kelurahan Cepoko that is Ibu Ismiyati took the initiative to make processed foods made from milk. Mrs. Ismiyati as a pioneer of milk sticks production business that is personal with employ 5% of women PKK group. Dairy products that have been done just limited to milk stick. Though dairy products have the potential to be developed in order to increase farmers’ income. One of the obstacles to the development of dairy products is the lack of mastery of information on production and marketing techniques by mothers, the limited knowledge and skills of mothers in the processing of milk into products worth selling, causing dairy products are less varied and not devel- oped. The methods undertaken to improve knowledge on milk-based food production techniques are socialization, training and monitoring. PKK ladies are very enthusiastic to follow the milk process- ing into a variety of food products that are proclaimed with the presence of mothers despite the rain, they still spend time attending training activities. PKK ladies become aware of the diversification of products based , and skilled in processing milk into various foods as well as skilled in the produc- tion manejemn such as kenmas and marketing processed products kamanan Participants want more follow-up is more real in terms of assistance and continuous monitoring and marketing of dairy- based food products broadly and poured in MoU between FMIPA and Gunungpati District